2006
DOI: 10.1207/s15516709cog0000_58
|View full text |Cite
|
Sign up to set email alerts
|

Processing Reflexives and Pronouns in Picture Noun Phrase

Abstract: Binding theory (e.g., Chomsky, 1981) has played a central role in both syntactic theory and models of language processing. Its constraints are designed to predict that the referential domains of pronouns and reflexives are nonoverlapping, that is, are complementary; these constraints are also thought to play a role in online reference resolution. The predictions of binding theory and its role in sentence processing were tested in four experiments that monitored participants' eye movements as they followed spok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 37 publications
0
55
1
Order By: Relevance
“…The first has to do with the question of whether core and exempt binding are in complementary distribution as assumed by Pollard and Sag (1992) and Huang and Liu (2001), or may be in an overlapping distribution (Pollard and Xue, 2001;Runner et al, 2002Runner et al, , 2006. The second has to do with whether structural prominence can facilitate the identification of logophoric antecedents in LD exempt binding.…”
Section: Interpretation Of Overall Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first has to do with the question of whether core and exempt binding are in complementary distribution as assumed by Pollard and Sag (1992) and Huang and Liu (2001), or may be in an overlapping distribution (Pollard and Xue, 2001;Runner et al, 2002Runner et al, , 2006. The second has to do with whether structural prominence can facilitate the identification of logophoric antecedents in LD exempt binding.…”
Section: Interpretation Of Overall Resultsmentioning
confidence: 99%
“…If caki-casin is licensed as an exempt anaphor only when local antecedents are unavailable-in other words, if exempt binding is found only in contexts where core binding fails as assumed in Pollard and Sag (1992) and Huang and Liu (2001)-subjects should show a strong preference for local binding (i.e., Cenghyeni) in this sentence type. However, if core and exempt binding are not in complementary distribution (Pollard and Xue, 2001;Iida, 1992;Runner et al, 2002Runner et al, , 2006, subjects might still accept long-distance binding.…”
Section: Domain For Core Vs Exempt Bindingmentioning
confidence: 99%
“…This contrast is captured by the structural differences between possessive and nominative NPs: in (4), the nominative NP c-commands the reflexive in its local domain, but the possessive does not (Chomsky 1981;Reinhart & Reuland 1993). Processing studies have demonstrated the GMME for grammatically licit antecedents of reflexives, while an equivalent mismatch effect is not observedor is observed only after some delay-for grammatically illicit antecedents of reflexives (Sturt, 2003), although such non-grammatical antecedents can cause competition effects (Badecker & Straub, 2002;Runner et al, 2003Runner et al, , 2006.…”
Section: ) Exemplifies This Assumptionmentioning
confidence: 99%
“…This is just what one would expect if referential dependencies are interpreted at the first opportunity (immediately, in these patterns). More recent work (e.g., Sturt 2003, Runner et al 2006 confirms the promptness with which the processor acts on referential dependencies.…”
Section: Processingmentioning
confidence: 83%